2015
DOI: 10.5306/wjco.v6.i6.207
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironment and endocrine resistance in breast cancer: Friend or foe?

Abstract: Breast cancer affects one in eight women around the world. Seventy five percent of these patients have tumors that are estrogen receptor positive and as a consequence receive endocrine therapy. However, about one third eventually develop resistance and cancer reappears. In the last decade our vision of cancer has evolved to consider it more of a tissuerelated disease than a cell-centered one. This editorial argues that we are only starting to understand the role the tumor microenvironment plays in therapy resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…However, a high percentage of patients develop resistance, and up to one third of them have cancer recurrence within 15 years [106]. Previous studies suggest that hormone therapy could modulate TME which then induces treatment resistance.…”
Section: Hormonal Therapymentioning
confidence: 99%
“…However, a high percentage of patients develop resistance, and up to one third of them have cancer recurrence within 15 years [106]. Previous studies suggest that hormone therapy could modulate TME which then induces treatment resistance.…”
Section: Hormonal Therapymentioning
confidence: 99%
“…Interestingly, in an in vitro model, EGF and FGF have been shown to drive breast cancer cell resistance to letrozole via activation of the PI3K signaling pathway [ 55 ]. Other studies have shown that the cytokine IL-1β activates ER transcriptional activity and modulates response to 4-OH-tamoxifen, rendering it an agonist instead of an antagonist (reviewed in [ 59 ]). Other studies also suggest that stromal and immune cells within the tumor microenvironment may play a role in promoting endocrine resistance (reviewed in [ 59 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that the cytokine IL-1β activates ER transcriptional activity and modulates response to 4-OH-tamoxifen, rendering it an agonist instead of an antagonist (reviewed in [ 59 ]). Other studies also suggest that stromal and immune cells within the tumor microenvironment may play a role in promoting endocrine resistance (reviewed in [ 59 ]). And finally, Bernoulli et al have recently described a mouse model in which estrogen supplementation is required to support the growth of orthotopic ER+ MCF-7 primary tumors, but not ER+ MCF-7 lesions in the skeleton [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is a major contributor to hormone resistance [200,201], which is in part through stimulation of BCSCs. In this regard, gene expression profiling of MCF7-derived BCSCs shows an upregulation of inflammatory cytokines (like IL8) [202].…”
Section: Mechanisms Underlying Bcsc Enrichment Following the Develmentioning
confidence: 99%